Reinduction of PD1-inhibitor therapy: first experience in eight patients with metastatic melanoma. Issue 4 (August 2017) - Blasig, Hanna; Bender, Carolin; Hassel, Jessica C.; Eigentler, Thomas K.; Sachse, Michael M.; Hiernickel, Julia; Koop, Anika; Satzger, Imke; Gutzmer, Ralf
Abstract : Significant progress has been made in the treatment of metastatic melanoma during the last years. Approval of immune-checkpoint inhibitors and targeted therapies has been achieved recently. The sequencing of these therapies is an important issue. Here, we report our experience with the treatment and retreatment with PD1-inhibitors (PD1i) in eight patients. The patients (two female and seven male with a median age of 70 years, all melanoma stage IV, M1c) underwent a first treatment period with PD1i for a median of 5.5 months. Three (37.5%) patients had a stable disease as best response, two (25%) showed progression, two (25%) showed partial response, and one (12.5%) achieved complete remission. PD1i was discontinued due to disease progression in seven patients and due to side effects (pancreatitis) in one patient. Patients were subsequently treated with ipilimumab ( n =2), or chemotherapy ( n =4), or no other medical treatment ( n =2). All eight patients were subsequently retreated with PD1i for a median of 2.5 months. One (12.5%) developed a partial response, whereas in three patients (37.5%) the disease was stabilized. PD1i have shown a high and durable response rate in the first-line treatment of metastatic melanoma. Our study suggests PD1i retreatment as a reasonable option for selected patients. Further investigations are needed to verify the value of PD1i re-exposure and to identify subgroups of patients who can benefit.